Microstructure Analysis and Thermal Characteristics of NiTiHf Shape Memory Alloy with Different Composition - Buytoz, S.; Dagdelen, F.; Qader, I. N.; Kok, M.; Tanyildizi, B. (Korean Inst Metals Materials, 2021)
Improving shape memory alloys in term of microstructural analysis is important for some related applications. In this study, three different NiTiHf shape memory alloys were produced from high pure elements and by utilizing arc-melting device. The morphologies of different precipitations and microstructures were analyzed by optical microscope, mapping, and EDX compositional analysis. The DSC measurements showed that the phase transformation temperatures is increased by adding more hafnium instead of nickel content in NiTiHf alloy, however, the enthalpy change for both endo/exothermic process were decreased. Also, XRD analysis has been carried out for all alloys to find different phases, and to obtain grain size as a function of different composition of Ni and Hf elements. The oxidation shows that titanium dioxide (TiO2) is spread out over the surface, but the microstructures are completely different for each case, e.g. needle-like shapes (nanorods) has extended over the surface of Alloy A with 3 at% Hf, but plate-like Ti-rich microstructures is dominated on the surface of Alloy B that has twice as more Hf as Alloy A; on the other hand, Alloy C with 9 at% Hf has some precipitates with TiO phase. Graphic
Keywords: Shape memory alloy; NiTiHf; Thermal analysis; Microstructure